Case report: Sublingual mucinosis in a dog - Tinto, Debora; Tassani, Chiara; Di Benedetto, Matteo; Sabattini, Silvia; Capitani, Ombretta (Frontiers in Veterinary Science, 2022)
A 11-month-old male intact Shar-Pei (26.5 kg) was presented for a bilateral sublingual swelling of 4 months duration. The exploration of the oral cavity highlighted the presence of bilateral sublingual swellings, primarily consistent with bilateral ranula. The bilateral disease was treated with two subsequent surgeries four weeks apart. During the surgery, after removing an elliptical portion of the mucosa of the sublingual swelling, the presence of gelatinous tissue was visualized, and no saliva was present. The result of histological exam was oral mucinosis. At the subsequent follow-up the dog was in excellent conditions, without any symptoms. One month after the last operation, the dog underwent a visit in sedation to better evaluate the oral cavity. Both surgical sites were well healed and without the presence of relapses. Upon eight months follow-up the patient remained free of disease. This is the first reported case of oral mucinosis in sublingual mucosa in dogs. In this case the surgical treatment was curative.